The influence of the problem based instruction learning model on reasoning ability and mathematics learning outcomes on the system of linear equations with two variables - Nasution, Juwita Andriani; Harahap, Amin; Pasaribu, Laili Habibah (Desimal: Jurnal Matematika, 2024)
This study aims to see the influence of the problem-based teaching learning model on reasoning abilities and the results of mathematical learning in the materials of the two-variable linear equation system in class X of SMK Swasta Dewi Sartika Bilah. This research is quantitative research with a Quasi-experimental approach using a Pre-Test-Post-Test Control Group Design research design. The population in this study is all students of class X which consists of 3 classes namely X-TBSM, X-TKJ, While the sample in this study is class X-TKJ which consists of 30 students as an experimental class, and class X-OTKP. consisting of 30 students as a control class with a sampling technique that is Simple Random Sampling. The data collection technique used in this research is a test to obtain data on mathematical reasoning abilities and mathematical learning outcomes. The results of the data analysis process prove that there is a significant influence with the application of the problem-based teaching learning model on reasoning abilities and the results of mathematical learning in the materials of the two-variable linear equation system.